Is the concept of epistemic injustice useful for criminal procedures? - Coloma Correa, Rodrigo (2023)
This article addresses the question of whether the concept of epistemic injustice is useful in the evaluation of the design of criminal procedures. The irruption of this concept makes special sense in a scenario in which jurists show a growing interest in epistemology. The exercise of translation of the latter towards the legal, however, has been incomplete, since its social and ethical dimensions have been neglected. Recent clarifications of the contours of epistemic injustice, lead towards paying attention to issues structural in nature. The concept thus exhibits its potential to rethink criminal procedures, both from its methodological and symbolic dimension, especially if attention is paid to the notion of epistemic agency.